New Perspectives on Critical Marketing and Consumer Society - Ritch, Elaine L., editor 647022; McColl, Julie, editor 647023; Emerald Publishing Limited (Online service) issuing body 646680 (Bingley, U.K. : Emerald Publishing Limited, 2021)
Digital communication has altered the flow of global information, evolved consumer values and changed consumption practices worldwide. New Perspectives on Critical Marketing and Consumer Societyprovides an illuminating, challenging and thought providing guide for all upper-level students of marketing, branding and consumer behaviour.